Comparison of microparticle manipulating characteristics of canonical vortex beam and power-exponent-phase vortex beam. Issue 4 (23rd February 2021) - Pei, Zhonghua; Huang, Sujuan; Chen, Yi; Yan, Cheng
Abstract : We have experimentally studied the stable trapping and rotation of silica microspheres using canonical vortex (CV) beam and power-exponent-phase vortex (PEPV) beam. Numerical simulation was carried out to characterize the focusing property of these two types of beams. The dynamics of the microspheres in the two types of beams with various topological charges was investigated in detail. It shows that the precise control of microspheres in one direction can be realized. Furthermore, by optical trapping and moving the microspheres in the focus of the PEPV beam, it is proven that the velocity of the microspheres does not increase with the increase in the power order of the spiral phase and constant topological charge. We demonstrate the advantages and flexibility of PEPV beam for optical trapping applications. Optical manipulation technology based on PEPV beam may be used beneficially in optical tweezers and in applications for guiding microparticles.